2014
DOI: 10.1093/qjmed/hcu136
|View full text |Cite
|
Sign up to set email alerts
|

The association between chronic obstructive pulmonary disease and Parkinson’s disease: a nationwide population-based retrospective cohort study

Abstract: This nationwide retrospective cohort study demonstrates that PD risk is significantly increased in patients with COPD compared with those of the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…In this current study, no association was documented between β2‐agonists and risk of PD. However, COPD patients are intrinsically different from the general population; for one, they have a much higher risk of developing PD compared with the general population 11 ; also, COPD patients use β 2 ‐agonists much more frequently. Such intrinsic differences prevent direct comparison of the current results to those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this current study, no association was documented between β2‐agonists and risk of PD. However, COPD patients are intrinsically different from the general population; for one, they have a much higher risk of developing PD compared with the general population 11 ; also, COPD patients use β 2 ‐agonists much more frequently. Such intrinsic differences prevent direct comparison of the current results to those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their pharmacological role in relaxing airway muscles, long‐acting β 2 ‐agonists (LABAs) such as salmeterol and formoterol, provide sustained bronchodilation, while short‐acting β 2 ‐agonists (SABA) such as albuterol, fenoterol and terbutaline, are typically used as rescue medications due to their short duration of action 10 . Being the most prevalent users of β 2 ‐agonists, COPD patients have a 1.4 times higher risk of developing PD 11 possibly due to the impairment of gas exchange and the subsequent hypoxemia and hypercapnia 12 . Therefore, the COPD population may benefit significantly from the neuroprotective effects, if any, of β 2 ‐agonists.…”
mentioning
confidence: 99%
“…But in contrast, if pulmonary diseases were diagnosed only later in life, an inverse relationship with cognitive impairment was observed [46]. Similarly for other neurodegenerative disorders, a population-based study which evaluated the relationship between COPD and Parkinson's disease found the highest risk for COPD on incident Parkinson's disease in subjects under the age of 65 years [47]. Since incidence rates of neurodegenerative disorders generally increase with age, potential explanations might be that COPD effects are overruled in the course of time by age effects or that elderly with COPD prone to neurodegenerative disorders do not reach high age.…”
Section: Cognitive Impairment (Dementia)mentioning
confidence: 99%
“…Both PINK1 and PRKN gene mutations associated with mitochondrial dysfunction have been implicated in the development of hereditary recessive early-onset Parkinsonism [8][9][10]. A retrospective cohort study evaluating the clinical connection between Parkinson disease and COPD shows higher risk of developing Parkinson disease in COPD cases [11]. A recent paper demonstrates PRKN deficiency is related to increased inflammation and genomic instability, which can be involved in COPD pathogenesis [12].…”
Section: Introductionmentioning
confidence: 99%